2007
DOI: 10.1523/jneurosci.1182-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Connections between Layer 5B Pyramidal Neurons in Mouse Somatosensory Cortex Are Independent of Apical Dendrite Bundling

Abstract: Rodent somatosensory barrel cortex is organized both physiologically and anatomically in columns with a cross-sectional diameter of 100 -400 m. The underlying anatomical correlate of physiologically defined, much narrower minicolumns (20 -60 m in diameter) remains unclear. The minicolumn has been proposed to be a fundamental functional unit in the cortex, and one anatomical component of a minicolumn is thought to be a cluster of pyramidal cells in layer 5B (L5B) that contribute their apical dendrite to distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 75 publications
2
56
0
Order By: Relevance
“…These pioneering observations raised the possibility that the septal region is a special passage site in layer 4. This possibility was reinforced by other previous studies demonstrating that apical dendrites of layer 5 pyramidal neurons also locate preferentially to the septal region in mice and rats (Escobar et al, 1986;Ito, 1992;White and Peters, 1993;Krieger et al, 2007) and that thalamocortical axons from POm are predominantly found in the septal region of the rat cerebral cortex (Koralek et al, 1988). Our results further support this possibility.…”
Section: Whisker-related Patterns Of Intracortical Connectionssupporting
confidence: 89%
“…These pioneering observations raised the possibility that the septal region is a special passage site in layer 4. This possibility was reinforced by other previous studies demonstrating that apical dendrites of layer 5 pyramidal neurons also locate preferentially to the septal region in mice and rats (Escobar et al, 1986;Ito, 1992;White and Peters, 1993;Krieger et al, 2007) and that thalamocortical axons from POm are predominantly found in the septal region of the rat cerebral cortex (Koralek et al, 1988). Our results further support this possibility.…”
Section: Whisker-related Patterns Of Intracortical Connectionssupporting
confidence: 89%
“…We recorded simultaneously from up to 12 thick-tufted layer 5 pyramidal neurons in somatosensory cortical slices (300 μm thick) from Wistar rats (postnatal days [14][15][16] (Fig. 1 A and B)-a model system extensively used in previous studies of cortical neurons and plasticity (39,40,(45)(46)(47)(53)(54)(55)(56)(57)(58). Connectivity was determined by applying trains (5-15 spikes at 20-70 Hz) of pulses of current (∼2 nA for 2.5-4 ms) to each recorded neuron and measuring the response of the other neurons, in the form of excitatory postsynaptic potentials (EPSPs), in current-clamp mode ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two-photon microscopy has enabled the visualization of neocortical layer five pyramidal cells in living mice (Krieger et al 2007;Berglund et al 2008). This approach has been extended to image cerebellar granule cells in vivo ).…”
Section: In Vivo Imagingmentioning
confidence: 99%